2012
DOI: 10.1245/s10434-012-2263-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Folate Receptor β–expressing Tumor-associated Macrophages in Pancreatic Cancer

Abstract: FRβ+ macrophages are a novel subset of tumor-associated macrophages in pancreatic cancer and may play an important role in the tumor microenvironment in association with systemic metastasis through the interaction with tumor cells and vessels. FRβ+ macrophages may be promising a targeting therapy for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 32 publications
3
88
0
Order By: Relevance
“…The fluorescence measured in the noncancerous lymph nodes was likely due to OTL38 binding to activated macrophages, which express FRb (27)(28)(29)(30). However, the formation of OTL38 aggregates and Clinical Cancer Researchnonspecific uptake by lymph nodes is unlikely, as dissolving the agent at 7.5 mmol/L in 5% dextrose did not lead to the formation of measurable aggregates.…”
Section: Discussionmentioning
confidence: 95%
“…The fluorescence measured in the noncancerous lymph nodes was likely due to OTL38 binding to activated macrophages, which express FRb (27)(28)(29)(30). However, the formation of OTL38 aggregates and Clinical Cancer Researchnonspecific uptake by lymph nodes is unlikely, as dissolving the agent at 7.5 mmol/L in 5% dextrose did not lead to the formation of measurable aggregates.…”
Section: Discussionmentioning
confidence: 95%
“…folate receptor beta (FR-β) and VEGF and that mainly resided perivascularly and in the invasive front of the tumor [122].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(69,72) Clinical research has confirmed that M2-polarized TAMs are associated with poor prognoses in several cancers, including classical Hodgkin's lymphoma (CHL), (73) lung adenocarcinoma, (74) and pancreatic cancer. (75) Ding, et al (76) found a significant correlation between the expression of CD68 or CD163 protein with a tumor size, lymph node metastasis, and vascular invasion in patients with pancreatic cancer consistent with the role of TAM in ltration in pancreas and the promotion of pancreatic cancer development.…”
Section: Tumor Metastasismentioning
confidence: 76%